JUDICIAL CONTROL OF COURT OF AUDITORS ’DECISIONS. WHAT ARE THE LIMITS OF THE COURT OF AUDITORS ’PERFORMANCE? - Carlos Ramos Gomes, Eliton (Revista Gênero e Interdisciplinaridade, 2021)
The objective of this article was to discuss the judicial control of the decisions of the courts of auditors, as well as their limits of performance. The methodology used was the bibliographic research, having as sample books and legal journals that deal with the theme, the search was carried out in physical and online libraries. The discussion of the work revolved around the history of the courts of accounts in some countries, with the Court of Accounts of France being highlighted, as it is the model followed by the Brazilian TCU. It discusses the chronological evolution of the formation of the Court of Accounts in Brazil, from the time of colonization to the edition of the Federal Constitution of 1988, showing the organizational structure and performance of the TCU, within the scope of Article 71 of the Federal Constitution of 1988 Also, the functions of the Courts of Accounts are described, which are to supervise, consult, inform, judge, sanction, correct, standardize and listen, educate and guide. Still, the judicial performance of the courts of Auditors is demonstrated, exemplifying with doctrinal and jurisprudential citations, regarding the judicial control of the decisions of the courts of accounts, an overview of the doctrinal and jurisprudential understandings is presented, showing cases of review of the decisions of the Courts of Accounts by the Judiciary. It was concluded that the modern jurisprudence innovated when reviewing judgments of the Court of Auditors based on the principles of proportionality, morality, efficiency and theory of the determinant reasons, as well as the principle of unfastening jurisdictional protection. Finally, the Courts of Accounts can have their decisions reviewed by the Judiciary, both in formal and material aspects.